ECO-INDUSTRIAL DEVELOPMENT AS A CIRCULARIZATION POLICY FRAMEWORK TOWARD SUSTAINABLE INDUSTRIAL CITIES. LESSON AND SUGGESTIONS FROM THE ECO TOWN PROGRAM IN JAPAN - Fujita, Tsuyoshi; Ohnishi, Satoshi; Liang, Dong; Fujii, Minoru (BDC. Bollettino Del Centro Calza Bini, 2013)
Eco-industrial development is widely considered as an effective policy and a business concept to realize sustainable circularization through collaborative networks among industries. Japanese government has accumulated practices as its national Eco Town Program in 26 cities since 1997. The operation of facilities and policy implementation have provided lessons and suggestions particularly for industrializing cities who desperately seek for the sustainable solutions achieving environment management and economic growth simultaneously. This paper aims to review the policy framework as well as accomplishments of the Eco Town Program and to provide lessons and suggestions for industrial cities’ management. We reviewed and analyzed the experience of the Eco Town Program for a decade from viewpoints of the policy framework and circular situation; and provided general implications such as combination of recycle technologies and social system, symbiotic network among recycle entities and energy intensive industries as well as suitable locational planning.